Digitalisasi Kewirausahaan Siswa SMK Letris Indonesia 2 Menggunakan Metode SDLC Waterfall Melalui Pengembangan Website Penjualan Produk Lokal Sekolah - Ahmad Khoerul Riski; Firman Aziz Saputra; Muhammad Fiqri Dwi Saputra; Muhammad Pahri; Najmi Cipta Nugraha; Rika Julia Dewi; Zaki Arfa Mustafa; Ines Heidiani Ikasari (CV. Multi Kreasi Media, 2026)
Vocational High Schools (SMK) play a crucial role in preparing competent and entrepreneurial graduates. SMK Letris Indonesia 2 actively encourages students to produce various local products, but product promotion and sales are still conducted conventionally and not yet integrated into an official digital platform. This situation results in limited marketing reach, a lack of product documentation, and limited student experience in digital entrepreneurship. This activity aims to digitize student entrepreneurship through the development of a website selling the school's local products using the Waterfall System Development Life Cycle (SDLC) method. This method includes the stages of needs analysis, system design, implementation, testing, socialization, and evaluation. The results of the activity indicate that the school's website selling local products has been successfully developed and can be used as a digital-based promotional and marketing tool. The application of the Waterfall SDLC method resulted in a structured system that meets user needs. Furthermore, this activity provides students with hands-on experience in digital entrepreneurship, enhances their understanding of technology-based marketing, and supports the enhancement of the school's digital image and portfolio. Thus, the development of this website is expected to serve as a means of continuous learning and support the development of student entrepreneurship at SMK Letris Indonesia 2.